Molecular Characterization and Dietary Regulation of Glutaminase 1 (gls1) in Triploid Crucian Carp (Carassius auratus) - Yangbo Xiao; Rong Huang; Shenping Cao; Dafang Zhao; Zhuangwen Mao; Chuchu Xiao; Zhehua Xu; Xiaomei Zhou; Xinran Zhang; Yu Zhang; Jianzhou Tang; Junyan Jin; et al. (Fishes, 2022)
Kidney-type glutaminase, encoded by the gls1 gene, plays a critical role in glutamate production and improvement of meat flavor. In this study, a gls1 gene encoding 595 amino acids was cloned from triploid crucian carp (Carassius auratus) (TCC) and showed a high similarity with the gls1 gene found in Cyprinus carpio, Sinocyclocheilus rhinocerous and Puntigrus tetrazona. Comparing the abundance of gls1 in different tissues, we found its expression level in the brain and liver were significantly higher than that in heart, gut, kidney, spleen and muscle. gls1 expression in the brain reached the highest value. In addition, the expression levels of gls1 also appeared different in diurnal variation, with the highest expression seen at 9:00, while it was low at 3:00, 6:00, 15:00 and 24:00. Furthermore, dietary regulation of gls1 expression was investigated in our study. In each feeding trial, each diet was randomly assigned to triplicate tanks. Fish were fed one of the tested diets up to satiation twice daily. The results showed that gls1 expression increased in 32% protein group and decreased in 35–41% protein group. The results of different protein source experiments showed that the expression of gls1 gene in the mixed protein group (the control group) was significantly higher than that in the fish meal and soybean meal groups. Glutamate treatment revealed that appropriate concentrations (0.10 mg/mL in vivo and 2.00% in vitro) of glutamate remarkably improved the expression of gls1. Besides, diets supplemented with 0.80–1.60% lysine-glutamate dipeptide exhibited a down regulatory impact on gls1 expression. In conclusion, this study demonstrated that the expression of gls1 in TCC was increased by 32% protein diet, mixed protein source diet and diet with 2.00% glutamate concentration, while decreased by 0.80–1.60% lysine-glutamate dipeptide. The findings of this study provide a reference for the regulation of gls1 and have a potential application in the optimization of dietary formula in aquaculture.

Extracellular Mitochondria Activate Microglia and Contribute to Neuroinflammation in Traumatic Brain Injury - Chaonan Zhang; Chuan Liu; Fanjian Li; Mutian Zheng; Yafan Liu; Lei Li; Huaijin Yang; Shu Zhang; Chongjin Wang; Hongtao Rong; Hui Guo; Ying Li; et al. (Neurotoxicity Research, 2022)

Improved lithium-ion batteries with coral-like anodes made of recycled spherical porous silicon coated with nitrogen-doped carbon - Zhao Zhang; Fengshuo Xi; Xiuhua Chen; Shaoyuan Li; Wenhui Ma; Zhao Ding; Tao Qu; Yongnian Dai; Rong Deng (Environmental Chemistry Letters, 2022)

Study on the Relationship Between Diet, Physical Health and Gut Microflora of Chinese College Students - Xiafen Hu; Jiaqi Guo; Jiadun Wang; Wanxin Liu; Xiaochen Xiang; Siyang Chen; Xinquan Li; Jinhan Tang; Wei Zhang; Hui Chen; Rong Shu; Qingming Wu; et al. (Current Microbiology, 2022)

Current Situation and Ecological Effects of Microplastic Pollution in Soil - Minggu Zhang; Miaomiao Tan; Rong Ji; Ronghui Ma; Chengliang Li (Reviews of Environmental Contamination and Toxicology, 2022)

Integration of transcriptomics and metabolomics reveals pathways involved in MDSC supernatant attenuation of TGF-β1-induced myofibroblastic differentiation of mesenchymal stem cells - Yin Celeste Cheuk; Xinhao Niu; Yongxin Mao; Jiawei Li; Jiyan Wang; Shihao Xu; Yongsheng Luo; Weixi Wang; Xuanchuan Wang; Yi Zhang; Ruiming Rong (Cell and Tissue Research, 2022)

Characteristics of antibiotic resistance gene distribution in rainfall runoff and combined sewer overflow - Xin-rong Pan; Lei Chen; Li-ping Zhang; Jian-e Zuo (Environmental Science and Pollution Research, 2022)

Ammonium induces oxidative stress, endoplasmic reticulum stress, and apoptosis of hepatocytes in the liver cell line of grass carp (Ctenopharyngodon idella) - Zhenyi Hu; Dengfeng Han; Tingting Zhang; Dapeng Li; Rong Tang (Environmental Science and Pollution Research, 2022)

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

Plasma Exo-miRNAs Correlated with AD-Related Factors of Chinese Individuals Involved in Aβ Accumulation and Cognition Decline - Lifang Wang; Hefu Zhen; Yuzhe Sun; Shuang Rong; Benchao Li; Zhijie Song; Zhili Liu; Zhiming Li; Jiahong Ding; Huanming Yang; Xiuqing Zhang; Haixi Sun; et al. (Molecular Neurobiology, 2022)
Numerous studies have investigated the risk factors of Alzheimer’s disease (AD); however, AD-risk factors related miRNAs were rarely reported. In this study, AD-risk factor related miRNAs of 105 Chinese individuals (45 AD patients and 60 cognitively normal controls) were investigated. The results showed that Hsa-miR-185-5p, Hsa-miR-20a-5p, and Hsa-miR-497-5p were related to AD and education, Hsa-miR-185-5p, Hsa-miR-181c-5p, Hsa-miR-664a-3p, Hsa-miR-27a-3p, Hsa-miR-451a, and Hsa-miR-320a were related to AD and depression. Target prediction of above miRNAs showed that these miRNAs were involved in the generation and clearance of amyloid-beta (Aβ), important molecules related to cognition, and disease-activated microglia response to AD. It is worth noting that Hsa-miR-185-5p was related to both education and depression, whose decreased expression pattern in AD patients was alleviated by education and enhanced by depression, and participates in Aβ generation and accumulation. Our results indicated that certain education and depression factors can contribute to AD progression by modulating miRNA expression, implying that preventive interventions might alter AD progression in Chinese patients.

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Homozygous missense mutation in CCDC155 disrupts the transmembrane distribution of CCDC155 and SUN1, resulting in non-obstructive azoospermia and premature ovarian insufficiency in humans - Huan Wu; Xin Zhang; Rong Hua; Yuqian Li; Li Cheng; Kuokuo Li; Yiyuan Liu; Yang Gao; Qunshan Shen; Guanxiong Wang; Mingrong Lv; Yuping Xu; et al. (Human Genetics, 2022)

Occurrence and damage of epidemic fungal diseases in middle and late stages of sugarcane growth in Yunnan Province of China - Wen-Feng Li; Xiao-Yan Wang; Hong-Li Shan; Rong-Yue Zhang; Yin-Hu Li; Wen-Jie Lu; Ying-Kun Huang (European Journal of Plant Pathology, 2022)

Concentrations, distribution, and risk assessment of endosulfan residues in the cotton fields of northern Xinjiang, China - Yang Zhang; Rong Guo; Yang Li; Mingyu Qin; Jingquan Zhu; Zhihong Ma; Yong Ren (Environmental Geochemistry and Health, 2022)

Biocrust diazotrophs and bacteria rather than fungi are sensitive to chronic low N deposition - Xiaoying Rong; Xiaobing Zhou; Xiangzhen Li; Minjie Yao; Yongxing Lu; Peng Xu; Benfeng Yin; Yonggang Li; Zachary T. Aanderud; Yuanming Zhang (Environmental Microbiology, 2022)
Anthropogenic long‐term nitrogen (N) deposition may dramatically impact biocrusts due to the overarching N limitation of soil biota in deserts. Even low levels of N may reach a critical loading threshold altering biocrust constituents and function. To identify the impact of chronic and continuous low levels of N deposition on biocrusts, we created a realistic gradient mirroring anthropogenic N addition rate (2:1 NH 4 + : NO 3 − rates: 0.3, 0.5, 1.0, 1.5, 3 g N m −2 yr −1 ) and measured the response of bacteria and fungi within cyanobacterial‐dominated biocrusts over 8 years in a temperate desert, the Gurbantunggut Desert, China. We found that once N deposition reached 1.5 g N m −2 yr −1 biocrust bacterial communities, including diazotrophs, were altered while no such tipping point existed for fungi. Above the threshold, bacterial richness was enhanced, the relative abundance of Chloroflexi, FBP and Gemmatimonadetes was elevated, and diazotrophs shifted from being dominated by Nostocaceae and Scytonemataceae (Cyanobacteria) to free‐living Bradyrhizobiaceae (Alphaproteobacteria). Alternatively, the relative recovery of a few fungal species within the Lecanorales, Pleosporales and Verrucariales became either enriched or diminished due to N deposition. The chronic addition of N resulted in a dense and interconnected bacterial co‐occurrence network that accentuated a functional shift from networks dominated by phototrophic species within the Nostocaceae, Xenococcaceae, Phormidiaceae and Scytonemataceae (Cyanobacteria) to ammonia‐oxidizing species within the Nitrosomonadaceae (Betaproteobacteria) and nitrifying bacteria [i.e. Nitrospiraceae (Nitrospirae)]. Based on structural equation models, the effects of N additions on biocrust constituents were imposed through indirect effects on pH, soil electrical conductivity and ammonium concentrations. In summary, biocrust constituents are generally insensitive to chronic low levels of N depositions until rates reach above 1.5 g N m −2 yr −1 with diazotrophs being the most sensitive biocrust constituents followed by bacteria and finally fungi. Ultimately once the threshold is reached N deposition favours biocrust constituents utilizing inorganic N and other C sources over relying on phototrophic and/or N‐fixing cyanobacteria for C and N.

HOXD11 upregulates JAM-A and exerts oncogenic properties via NF-κB signaling pathway in esophageal squamous cell carcinoma - Rong Xiong; Qiongxian Long; Xuqian Zhang; Jun Xu; Yanqun Liu; Li Xiong; Siyun Yang; Gang Feng; Guiqing Song; Kang Liu (Human Cell, 2022)

Preparation of Pinocembrin-Loaded F127/MPEG-PDLLA Polymer Micelles and Anti-Osteoporotic Activity - Xia Cao; Qing He; Michael Adu-Frimpong; Xinyi Shen; Wanjing Rong; Xiaoxiao Li; Jian Zhang; Xiaoli Xia; Feng Shi; Hao Ji; Elmurat Toreniyazov; Qilong Wang; et al. (AAPS PharmSciTech, 2022)

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Tumor necrosis factor-α coordinates with transforming growth factor-β1 to induce epithelial-mesenchymal transition and migration via the NF-κB/NOX4 pathway in bronchial epithelial cells - Ke Li; Rong Zhou; Mingze Ma; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Fang Zhou (Molecular Biology Reports, 2022)

Phosphorylation of Truncated Tau Promotes Abnormal Native Tau Pathology and Neurodegeneration - Longfei Li; Yanli Jiang; Gang Wu; Yacoubou Abdoul Razak Mahaman; Dan Ke; Qun Wang; Bin Zhang; Jian-Zhi Wang; Hong-Lian Li; Rong Liu; Xiaochuan Wang (Molecular Neurobiology, 2022)

Tetramethylpyrazine protects neural stem cells against sevoflurane-induced toxicity through Akt/GSK-3β pathway - Yan Feng; Kui Wang; Ning Wang; Pengyu Jia; Lei Zhang; Haozheng Yuan; Pan Lu; Yang Lu; Hong Zhang; Rong Li; Yan Zhang; Qianqian Li; et al. (Metabolic Brain Disease, 2022)

Potential therapeutic strategies for myocardial infarction: the role of Toll-like receptors - Sumra Komal; Nimrah Komal; Ali Mujtaba; Shu-Hui Wang; Li-Rong Zhang; Sheng-Na Han (Immunologic Research, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Assessing the Impact of Atrazine on the Availability of Arsenic in Soils Using DGT Technique - Yanying Li; Liying Yan; Qiuyu Rong; Jun Luo; Hao Zhang; Kevin C. Jones (Bulletin of Environmental Contamination and Toxicology, 2022)

Prediction model for disc cutter wear during hard rock breaking based on plastic removal abrasiveness mechanism - Lei She; She-rong Zhang; Chao Wang; Zheng-qiao Wu; Lun-chuang Yu; Li-xin Wang (Bulletin of Engineering Geology and the Environment, 2022)

Mechanism of progressive failure of a slope with a steep joint under the action of freezing and thawing: model test - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Bo Lu; Xiao-ke Shen; Xiao-wei Wang; Jie-sheng Liu; Liang-liang Wu; Xin-zhou Zhang (Journal of Mountain Science, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Physiology, metabolism, antibiotic resistance, and genetic diversity of Harveyi clade bacteria isolated from coastal mariculture system in China in the last two decades - Hao Kang; Yongxiang Yu; Meijie Liao; Yingeng Wang; Guanpin Yang; Zheng Zhang; Bin Li; Xiaojun Rong; Chunyuan Wang (Frontiers in Marine Science, 2022)
Vibrio bacteria, particularly members of the Harveyi clade, are the most important pathogens of aquatic organisms that cause significant economic losses in the world. It is difficult to provide specific data on taxa of the Harveyi clade for biological research and prevention strategies. Therefore, we conducted an extensive phenotypic and antibiotic resistance study, as well as phylogenetic and molecular typing of 192 isolates of the Harveyi clade collection from 2000 to 2020 with a typical interannual difference from a coastal area in China. The isolates had a significant interspecific genetic and antibiotic resistance diversity. Based on the multilocus sequence analysis (MLSA) of housekeeping genes ( gyrB , pyrH , recA , and atpA ), 192 Harveyi clade isolates were rapidly and accurately classified into 10 species. The population of these isolates was composed of 95 sequence types (STs), of which 92 STs were newly identified, indicating a high degree of genetic diversity. ST327 ranked first, accounting for 11.5% of the total number of isolates (22 out of 192), followed by ST215 with 6.25%, while 63 STs included single isolates. At the metabolic level, the physiological and biochemical experiments revealed that all the Harveyi clade isolates were positive for oxidase and negative for melibiose. The isolates showed a varied tolerance to 11 antibiotics. No isolates were resistant to neomycin. The percentages of sulfadimidine-resistant strains (61 out of 192), sulfadiazine (44 out of 192), sulfamonomethoxine (44 out of 192), sulfamethoxazole (33 out of 192), thiamphenicol (34 out of 192), ciprofloxacin (52 out of 192), and enrofloxacin (31 out of 192) were 31.77%, 22.92%, 22.92%, 17.19%, 17.71%, 27.08%, and 16.15%, respectively. A proportion of 61.8% of the isolates presented a multiple antibiotic resistance index (MARI) lower than 0.1, indicating that the risk of antibiotic resistance transmission of most of the Harveyi clade is low in mariculture systems in China. These results provide substantial data to support further studies on the identification and genetic and metabolic diversity of Harveyi clade isolates in mariculture systems in China.

Antifungal and insecticidal activities of rhein derivatives: synthesis, characterization and preliminary structure–activity relationship studies - Xiang Zhu; Shunshun Chen; Yan Zheng; Yong Zhang; Tom Hsiang; Rong Huang; Jingwei Qi; Tian Gan; Yue Chang; Junkai Li (Natural Product Research, 2022)

Protective Effect of Selenium on the Oxidative Damage of Kidney Cells Induced by Sodium Nitrite in Grass Carp (Ctenopharyngodon idellus) - Tingting Zhang; Chaorui Yao; Zhenyi Hu; Dapeng Li; Rong Tang (Biological Trace Element Research, 2022)

Runoff projections of the Qinling Mountains and their impact on water demand of Guanzhong region in Northwest China - Zhao-peng Zhang; Ke-qin Duan; Huan-cai Liu; Ya-li Meng; Rong Chen; Da-wei Li; Shuang-shuang Li (Journal of Mountain Science, 2022)

Antimicrobial Resistance and Genotype Characteristics of Vibrio scophthalmi Isolated from Diseased Mariculture Fish Intestines With Typical Inter-Annual Variability - Yongxiang Yu; Xiao Liu; Yingeng Wang; Meijie Liao; Miaomiao Tang; Xiaojun Rong; Chunyuan Wang; Bin Li; Zheng Zhang (Frontiers in Marine Science, 2022)
As an intestinal organism settled long-term within the gut of marine fish, Vibrio scophthalmi is a potential object for the bacterium genetic variation and adaptation research. The genetic diversity, antimicrobial resistance phenotype, and genotype of 33 V. scophthalmi isolated from diseased marine fish intestines between 2002 and 2020 were evaluated. The results showed that all isolates were frequently resistant to penicillins, cephalosporins, aminoglycosides, and macrolides and displayed multidrug-resistant (MDR) phenotype in vitro . Thirty percent of isolates were resistant to more than 20 different drugs. The average insensitive (resistant and intermediate) rate of V. scophthalmi isolates was 49.5%~81.8% between 2002 and 2020, but the t-test revealed that there was no significant difference in the drug-resistance rate of V. scophthalmi isolates with typical interannual variability. Eleven antimicrobial resistance genes ( strB , strA , ant(3 ˝)-I , mphA , blaPSE , qnrS , tetC , tetE , tetM , tetS , and int1 ) were detected in these isolates, but the antimicrobial resistance phenotypes and genotypes of these isolates were not consistent. Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) analysis indicated that 33 isolates could be divided into two clusters (G1 and G3) and two single isolates (G2 and G4), and the G2 cluster was isolated from South Sea C. undulates with typical geographical species differences. There was no significant correlation between the drug susceptibility and the genetic types of V. scophthalmi isolates. The results reveal the mismatch phenomenon between antimicrobial resistance and genotype of inherent V. scophthalmi in the marine fish intestines, and the antimicrobial susceptibility isolates might be a potential risk source for storage and transmission of resistance genes.

MoS2 boosts the Fe2+/PMS process for carbamazepine degradation - Huan Peng; Rong Chen; Ningyao Tao; Yangyi Xiao; Chenxing Li; Tuqiao Zhang; Miaomiao Ye (Environmental Science and Pollution Research, 2022)

Recognition of the Multi-class Schizophrenia Based on the Resting-State EEG Network Topology - Fali Li; Lin Jiang; Yuanyuan Liao; Cunbo Li; Qi Zhang; Shu Zhang; Yangsong Zhang; Li Kang; Rong Li; Dezhong Yao; Gang Yin; Peng Xu; et al. (Brain Topography, 2022)

Selenium Deficiency Induces Autophagy in Chicken Bursa of Fabricius Through ChTLR4/MyD88/NF-κB Pathway - Ruili Zhang; Qing Liu; Rong Guo; Di Zhang; Yang Chen; Guangxing Li; Xiaodan Huang (Biological Trace Element Research, 2022)

Dynamic p-y curves for vertical and batter pile groups in liquefied sand - Jian Zhang; Yurun Li; Xian Rong; Yan Liang (Earthquake Engineering and Engineering Vibration, 2022)

Bmal1- and Per2-mediated regulation of the osteogenic differentiation and proliferation of mouse bone marrow mesenchymal stem cells by modulating the Wnt/β-catenin pathway - Jiawen Zheng; Lanxin Zhang; Zhen Tan; Qing Zhao; Xiaoyu Wei; Yuqing Yang; Rong Li (Molecular Biology Reports, 2022)

Prediction of the sea buckthorn AQP gene structure and its spatiotemporal expression pattern under drought stress - Dan Zhang; Nanxiang Yang; Jiawei Dong; Cheng Wang; Qiangfeng Li; Rong Wang; Zhipeng Feng; Dejuan Xie; Guisheng Ye; Yuhua Ma (Journal of Plant Biochemistry and Biotechnology, 2022)

Comment on “Relationship of Circulating Copper Level with Gestational Diabetes Mellitus: a Meta-analysis and Systemic Review” - Shu-ping Li; Xiao-ping Zhang; Xin-hong Cui; Li-juan Zhao; Yan-jun Rong (Biological Trace Element Research, 2022)

How do precipitation events modify the stable isotope ratios in leaf water at Lhasa on the southern Tibetan Plateau? - Yong Wang; Wusheng Yu; Lun Luo; Minghui Li; Xiaoming Liu; Rong Guo; Yaoming Ma; Baiqing Xu; Guangjan Wu; Chengyi Zhao; Zhaowei Jing; Feili Wei; et al. (Isotopes in Environmental and Health Studies, 2022)

Ventromedial Thalamus-Projecting DCN Neurons Modulate Associative Sensorimotor Responses in Mice - Jie Zhang; Hao Chen; Li-Bin Zhang; Rong-Rong Li; Bin Wang; Qian-Hui Zhang; Liu-Xia Tong; Wei-Wei Zhang; Zhong-Xiang Yao; Bo Hu (Neuroscience Bulletin, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

HucMSC-Ex alleviates inflammatory bowel disease via the lnc78583-mediated miR3202/HOXB13 pathway - Yuting Xu; Li Zhang; Dickson Kofi Wiredu Ocansey; Bo Wang; Yilin Hou; Rong Mei; Yongmin Yan; Xu Zhang; Zhaoyang Zhang; Fei Mao (Journal of Zhejiang University-SCIENCE B, 2022)

A low-cost in-situ CO2 sensor based on a membrane and NDIR for long-term measurement in seawater - Meng Li; Baolu Du; Jinjia Guo; Zhihao Zhang; Zeyu Lu; Rong’er Zheng (Journal of Oceanology and Limnology, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Phytoremediation of uranium-contaminated soil by perennial ryegrass (Lolium perenne L.) enhanced with citric acid application - Lishan Rong; Shiqi Zhang; Jiali Wang; Shiyou Li; Shuibo Xie; Guohua Wang (Environmental Science and Pollution Research, 2022)

Quinolizidine alkaloids from the roots of Sophora flavescens - Jian-Chun Li; Zhi-Jun Zhang; Dan Liu; Ming-Yan Jiang; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2022)

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

A historical record of trace metal deposition in northeastern Qinghai-Tibetan Plateau for the last two centuries - Shanying Li; Weiwei Sun; Rong Chen; Zhijie Zhang; Dongliang Ning; Zhenyu Ni (Environmental Science and Pollution Research, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Pulsed exsolution of magmatic ore-forming fluids in tin-tungsten systems: a SIMS cassiterite oxygen isotope record - Yang Li; Rong-Qing Zhang; Sheng He; Massimo Chiaradia; Xian-Hua Li (Mineralium Deposita, 2022)

The establishment of giant panda (Ailuropoda melanoleuca) fibroblast cell line - Yuliang Liu; Jiasong Chen; Tongying Feng; Rong Hou; Zhigang Cai; Donghui Wang; Mingyue Zhang; Yuan Li; Yijiao Chen; Junhui An (In Vitro Cellular & Developmental Biology - Animal, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Study on the impact of comprehensive urbanization on urban civil building CO2 emissions in China - Rong Guo; Nan Li; Hailin Mu; Ming Zhang; Xiyue Yang; Yixuan Han; Rongkang Yao; Zhihao Shao (Environmental Science and Pollution Research, 2022)

A New Species of Paradiplozoon (Monogenea: Diplozoidae), A Gill Parasite of the Schizothorax Fish (Cyprinidae: Schizothoracinae) from the Yarkand River, Xinjiang, China - Kadirden Arken; Cui-Lan Hao; Ai-Ming Guo; Wen-Run Zhang; Meng-Jie Rong; Wuljan Kamal; Sheng-Li Tian; Munira Kadir; Cheng Yue (Acta Parasitologica, 2022)

Sediment Resuspension as a Major Contributor to Sinking Particles in the Northwestern South China Sea: Evidence From Observations and Modeling - Lihua Ran; Wentao Ma; Martin G. Wiesner; Yuntao Wang; Jianfang Chen; Lanlan Zhang; Zhi Yang; Jingjing Zhang; Hongliang Li; Jian Ren; Rong Xiang; Erick Fredj (Frontiers in Marine Science, 2022)
The lateral advection of sinking particles is a well-known phenomenon in the South China Sea (SCS) and has a significant impact on the estimation of the efficiency of the biological carbon pump. However, little is known about the sources and pathways of sinking particles. Here, we present benthic and freshwater diatom fluxes and relative abundances collected by a sediment trap deployed at a water depth of 1,000 m and more than 500 m above the seafloor in the northwestern SCS, indicating that laterally transported resuspended sediment accounts for a significant part of the particle flux to the deep sea. A Lagrangian particle tracking model (LPTM) revealed that the resuspended particles likely originated from the neighboring continental slope, approximately 12–145 km to the west of the study site. Sediment trap observations and the LPTM together indicated that the impact of resuspended sediment occurred mainly in the deep water, and especially strong sediment resuspension was related to summer monsoon-induced coastal upwelling. The results suggest that particle resuspension has an important impact on the biological pump as well as on paleoenvironmental reconstructions of the SCS.

A new prenylated 3-benzoxepin derivative with anti-influenza A virus activity from Elsholtzia penduliflora - Lu Zhang; Linyao Yang; Rong-Tao Li; Fei Yu; Jindong Zhong (Natural Product Research, 2022)

Activation of Autophagy Ameliorates Age-Related Neurogenesis Decline and Neurodysfunction in Adult Mice - Na Yang; Xueqin Liu; Xiaojie Niu; Xiaoqiang Wang; Rong Jiang; Na Yuan; Jianrong Wang; Chengwu Zhang; Kah-Leong Lim; Li Lu (Stem Cell Reviews and Reports, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Transgelin-2 interacts with CD44 to regulate Notch1 signaling pathway and participates in colorectal cancer proliferation and migration - Rong Ding; Guoyu Li; Yueyi Yao; Lijuan Zhang; Xuan Zhang; Jiayi Li; Tao Shen; Yi Gao; Tao Wu; Shuzhen Kong; Ming Huang; Yunfeng Li (Journal of Physiology and Biochemistry, 2022)

Understanding the key factors determining rural domestic waste treatment behavior in China: a meta-analysis - Donghui Zheng; Jing Shen; Rong Li; Bei Jian; Jihong Zeng; Yongliang Mao; Xiaoning Zhang; Pradipta Halder; Mei Qu (Environmental Science and Pollution Research, 2022)

An ocean modeling study to quantify wind forcing and oceanic mixing effects on the tropical North Pacific subsurface warm bias in CMIP and OMIP simulations - Yuchao Zhu; Rong-Hua Zhang; Delei Li (Climate Dynamics, 2022)

Association Between Essential Metal Elements and the Risk of Autism in Chinese Han Population - Jiahui Ma; Jing Wu; Haibin Li; Jingyu Wang; Jisheng Han; Rong Zhang (Biological Trace Element Research, 2022)

Selenium Deficiency Causes Inflammatory Injury in the Bursa of Fabricius of Broiler Chickens by Activating the Toll-like Receptor Signaling Pathway - Yu Bai; Ruili Zhang; Qing Liu; Rong Guo; Guangxing Li; Bin Sun; Di Zhang; Yang Chen; Xiaodan Huang (Biological Trace Element Research, 2022)

The anticancer potential of the dietary polyphenol rutin: Current status, challenges, and perspectives - Arakkaveettil Kabeer Farha; Ren-You Gan; Hua-Bin Li; Ding-Tao Wu; Atanas G. Atanasov; Khalid Gul; Jia-Rong Zhang; Qiong-Qiong Yang; Harold Corke (Critical Reviews in Food Science and Nutrition, 2022)

Sampling Designs for Monitoring Ichthyoplankton in the Estuary Area: A Case Study on Coilia mystus in the Yangtze Estuary - Xiangyu Long; Rong Wan; Zengguang Li; Dong Wang; Pengbo Song; Fan Zhang (Frontiers in Marine Science, 2022)
A fishery-independent survey can provide detailed information for fishery assessment and management. However, the sampling design for the survey on ichthyoplankton in the estuary area is still poorly understood. In this study, we developed six stratified schemes with various sample sizes, attempting to find cost-efficient sampling designs for monitoring Coilia mystus ichthyoplankton in the Yangtze Estuary. The generalized additive model (GAM) with the Tweedie distribution was used to quantify the “true” distribution of C. mystus eggs and larvae, based on the data from the fishery-independent survey in 2019–2020. The performances of different sampling designs were evaluated by relative estimation error (REE), relative bias (RB), and coefficient of variation (CV). The results indicated that appropriate stratifications with intra-stratum homogeneity and inter-stratum heterogeneity could improve precision. The stratified schemes should be divided not only between the North Branch and South Branch but between river and sea. No less than two stratifications in the South Branch could also get better performance. The sample sizes of 45–55 were considered as the cost-efficient range. Compared to other monitoring programs, monitoring ichthyoplankton in the estuary area required a more complex stratification and a higher resolution sampling. The design ideology and optimization methodology in our study would provide references to sampling designs for ichthyoplankton in the estuary area.

Regulation of β1-integrin in autophagy and apoptosis of gastric epithelial cells infected with Helicobacter pylori - Boqing Li; Qianyu Rong; Yunqiu Du; Ruiqing Zhang; Jing Li; Xiaohan Tong; Li Geng; Ying Zhang (World Journal of Microbiology and Biotechnology, 2022)

Promotional effect of ZrO2 and WO3 on bimetallic Pt-Pd diesel oxidation catalyst - Rongrong Fan; Zhaoqiang Li; Yu Wang; Yan Wang; Zhiyong Ding; Cheng Zhang; Na Kang; Xin Guo; Rong Wang (Environmental Science and Pollution Research, 2022)

Soil nutrient variability mediates the effects of erosion on soil microbial communities: results from a modified topsoil removal method in an agricultural field in Yunnan plateau, China - Ruihuan Zhang; Li Rong; Lanlan Zhang (Environmental Science and Pollution Research, 2022)

Experimental study of vertical and batter pile groups in saturated sand using a centrifuge shaking table - Zhang Jian; Li Yurun; Yan Zhixiao; Huang Da; Rong Xian; Liang Yan (Earthquake Engineering and Engineering Vibration, 2022)